2020
DOI: 10.20960/nh.03024
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility, safety and outcome of endoscopic gastrostomy in patients with esophageal cancer

Abstract: Introduction: Disease related malnutrition (DRM) affects at least one in four inpatients, increasing both morbidity and mortality during admission and after discharge. Nevertheless, its repercussion on hospital activity is not properly quantified. Objective: To determine the impact of an adequate coding of DRM and procedures employed to reverse it in the hospital average weight and other hospital indicators. Methods: Comparative study carried out in every patients requiring nutritional support and followed up … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…Several studies reported that the mean survival in the surgical gastrostomy group was 3–4 months; in the bypass group, it was 3–9.7 months; in the endoscopic gastrostomy group, it was 4–7 months; in palliative resection, it was 7.8–13 months; in (NdYaG) laser treatment, it was 7.2 months; and in the stent group, it was 2.9–6 months [ 24 , 25 , 27 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 ]. Regarding survival time, our results with laparogastroscopic procedure are encouraging and comparable to the above-mentioned methods.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies reported that the mean survival in the surgical gastrostomy group was 3–4 months; in the bypass group, it was 3–9.7 months; in the endoscopic gastrostomy group, it was 4–7 months; in palliative resection, it was 7.8–13 months; in (NdYaG) laser treatment, it was 7.2 months; and in the stent group, it was 2.9–6 months [ 24 , 25 , 27 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 ]. Regarding survival time, our results with laparogastroscopic procedure are encouraging and comparable to the above-mentioned methods.…”
Section: Discussionmentioning
confidence: 99%
“…(2) It is a technique with a medium learning curve, requiring competence in thoracic and abdominal surgery. (3) It avoids disabling surgical procedures used in open surgery or endoscopy (PEG (percutaneous endoscopic gastrostomy)) [ 38 , 44 , 45 , 46 , 47 ]. (4) Laparogastroscopy allows the assessment of the cancer stage to be performed with endoperitoneal visualization (during transtumoral drilling, biopsy material can be taken).…”
Section: Discussionmentioning
confidence: 99%
“…Enteral nutrition is recognized as the first choice for longterm nutritional support treatment. 10 For more than 30 days of nutritional support, the American Gastroenterology Association recommends percutaneous gastrostomy. 11 Most doctors support enteral nutrition therapy for elderly patients, and percutaneous gastrostomy should be considered if there are no contraindications.…”
Section: Discussionmentioning
confidence: 99%